Management of Change Inspired by the NAIP - Devakumar, C.; Rao, D. Rama; Pandey, P. S.; Ezekiel, R.; Srivastava, A. P.; Ramasundaram, P.; Misra, R. P.; Kochhar, Sudhir (Indian Farming, 2015)
The ICAR has truly shown the way for other leading institutionsand universities to systematically engage in developing toolkit ofpolicies, internal guidelines and manuals of operating procedures for each of the management aspects for the promotion of innovations and change management.